Effect of welding parameters on microstructure and mechanical properties of friction stir welded joints of 2060 aluminum lithium alloy. Issue 5 (November 2015) - Mao, Yuqing; Ke, Liming; Liu, Fencheng; Huang, Chunping; Chen, Yuhua; Liu, Qiang
Abstract Two-millimeter-thick 2060 Al-Li alloy plates were friction stir welded under a welding speed of 95–150 mm/min and rotation speed of 750–1500 rpm. The effects of welding speed and rotation speed on formation quality, microstructure, secondary phase particles' transformation, and mechanical properties of the joints were investigated. The results show that defect-free joints are produced for varying friction stir welding (FSW) parameters, and nugget size increases firstly and then decreases with increasing rotation speed or decreasing welding speed. The weld nugget zones (WNZs) have fine dynamically recrystallized grains, and the size decreases to 7.9 μm with increasing rotation speed to 1180 rpm or decreasing welding speed to 118 mm/min, while the grains are coarsened at 1500 rpm or 95 mm/min. A similar trend occurs in the transformation of secondary phase particles, whose size is the smallest in WNZ at 1180 rpm–118 mm/min. All joints exhibit softened zones where the hardness is the lowest, and the joints fracture from WNZs or heat-affected zones. The joints welded at 1180 rpm–118 mm/min perform the highest ultimate tensile strength of 495 MPa, yield strength of 380 MPa, and elongation of 10.2 %. With increasing rotation speed or decreasing welding speed, the strengths and elongation of the joints increase firstly and then decrease.